Humanistic Education as a Strategy for Student Character Development Students at SMK Bersama Berastagi - Ernawati Br Barus; Nasrul Nasrul; Romi Laspita (Journal of Community Service and Empowerment, 2026)
Character education is a fundamental aspect in developing a holistic and civilized student personality. However, learning practices in schools still tend to be oriented toward cognitive achievement, resulting in less attention being paid to affective aspects and human values. This community service activity aims to implement humanist education as a strategy for developing student character at SMK Bersama Berastagi. The implementation methods include outreach activities, participatory education, interactive discussions, and mentoring that emphasize human values ​​such as empathy, tolerance, responsibility, honesty, and cooperation. The participants were SMK Bersama Berastagi students, who were actively involved in the dialogic and reflective learning process. The results of the activity indicate an increase in students' understanding of the importance of character values, increased self-awareness and social sensitivity, and the development of more positive attitudes in social interactions and the school environment. Furthermore, this activity also provides practical insights for educators in implementing a humanist approach in daily learning. Thus, humanist education has proven effective as a strategy for strengthening student character and contributes to creating a more democratic, inclusive, and meaningful learning environment.